Ana Ilce Gómez: poetry asided to the mysterious silence - Zosa-Cano, Alexander (2024)
Ana Ilce Gómez Ortega is clearly Nicaragua’s greatest lyric poet. His Poetry is not the shipwreck, but it is the sailboat where loneliness and loneliness intersect everyday life of women. A sample of the poetryof Gómez Ortega, author of The ceremonies of silence (two editions: 1975 and 1989) and Poems of the Everyday Human (2004), is compiled briefly to present it to a Central American public. His work is the manifestation of a peaceful life away from of national developments, demonstrating the sobriety of their work and their commitment to poetry. His invocations between customs and mystery hang of the thread where the author builds herself in a self-demanded silence from where the image of the poet reaches its full dimension. Behold: Ana Ilce Gómez Ortega!